PEMANFAATAN REPOSITORY PERGURUAN TINGGI UNTUK MENUNJANG PENELUSURAN DAN TEMU KEMBALI INFORMASI MAHASISWA AL MA’ARIF : JURNAL ILMU PERPUSTAKAAN DAN INFORMASI ISLAM 2024 - Daulay, Rosniar; Hamdani, Selvia Yunita; Rahmi, Lailatur (UIN Imam Bonjol Padang, 2025)
Information retrieval constitutes a fundamental aspect in supporting academic activities at higher education institutions. In the digital era, institutional repositories play a pivotal role in storing and disseminating students' scholarly works in an open-access format. This study aims to analyze the extent to which Universitas Andalas’ repository, particularly the eskripsi application, facilitates students in searching and retrieving academic literature. Employing a quantitative descriptive approach with 98 student respondents, this research explores students’ perceptions regarding system usability, perceived usefulness, and encountered technical challenges. The findings reveal that the e-skripsi application significantly enhances the speed of information retrieval, supports the effective preparation of academic papers, and strengthens students' digital literacy skills. Nevertheless, certain obstacles were identified, such as decreased system performance during high traffic periods and the absence of advanced search features. Based on these insights, the study recommends strengthening technical infrastructure, developing a more interactive user interface, and integrating digital literacy programs to improve the repository’s effectiveness and sustainability within the university ecosystem